2013
DOI: 10.2478/aree-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Production From Amaranth Biomass

Abstract: Energy variety of amaranth (Amaranthus spp.) was grown in large-scale trials in order to verify the capability of its cultivation and use as a renewable energy source in a biogas plant. The possibility of biogas production using anaerobic co-fermentation of manure and amaranth silage was verified in the experimental horizontal fermentor of 5 m3 volume, working at mesophilic conditions of 38-40 °C. The goal of the work was also to identify the optimum conditions for growth, harvesting and preservation of amaran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The biomass and biogas potential of amaranth was investigated in several studies [6,18,20,[30][31][32][33][34]. Comparative studies evaluated whether amaranths are competitive with maize as a bioenergy crop and revealed that maize is superior to amaranth due to its high performance in both dry matter yield and content.…”
Section: Introductionmentioning
confidence: 99%
“…The biomass and biogas potential of amaranth was investigated in several studies [6,18,20,[30][31][32][33][34]. Comparative studies evaluated whether amaranths are competitive with maize as a bioenergy crop and revealed that maize is superior to amaranth due to its high performance in both dry matter yield and content.…”
Section: Introductionmentioning
confidence: 99%
“…The biofuel production from amaranth also has the advantages due to high and relatively stable harvests compared to most of the other bioenergy crops, and in small demands for intensification factors, resulting in low production costs. But the success depends on the choice of appropriate species, genotypes having higher biomass and higher cell wall polymer contents [10,19,24]. The third table displays previous research on different bioenergy crops and their percentages of cell wall polymers.…”
Section: Soybean As a Raw Materials For Bioenergy/bio-fuelmentioning
confidence: 99%
“…Under the long-day conditions of temperate Central Europe, photoperiod-sensitive amaranth genotypes delay flowering and display elongated vegetative growth. This observation prompted the evaluation of the biomass potential of amaranth in the context of biogas production, which revealed a promising performance and a potential for future improvement [16,[20][21][22][23][24][25]. In addition, amaranth can be used as a silage crop in both tropical and temperate regions, for which a high biomass is advantageous [14].…”
Section: Introductionmentioning
confidence: 99%